Effectiveness Of Guidance And Counselling Services Using Context-input-process-product Model: A Conceptual Framework. - Natesan, Manchelah A/P; Li, Lau Poh; Hutagalung, Fonny; Lim, Haslee Shahril (American Scientific Publishers, 2024)
Guidance and Counseling Services have become an important support service in secondary schools in Malaysia. The Ministry of Education, Malaysia has recognized the support service since 1996 as well as appointed counseling teachers on full-time basis in schools. These teachers are exempted from teaching and learning in the classroom. This service has been in force for the past 20 years. Today, almost all secondary schools across Malaysia have placed at least one full-time counseling teacher where he or she is required to plan and carry out the service effectively in schools. A recent comprehensive study on the effectiveness of the implementation of the service shows that the support service is still not effective. It is high time to reassess the true extent of the effectiveness of counseling teachers roles and function. Stufflebeam CIPP model, will be able to evaluate different aspects of a service or program to determine its effectiveness.